2019
DOI: 10.5312/wjo.v10.i7.278
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma for muscle injuries: A systematic review of the basic science literature

Abstract: BACKGROUND Platelet-rich plasma (PRP) is an increasingly used biologic adjunct for muscle injuries, as it is thought to expedite healing. Despite its widespread use, little is known regarding the mechanisms by which PRP produces its efficacious effects in some patients. AIM To clarify the effects of PRP on muscular pathologies at the cellular and tissue levels by evaluating the basic science literature. METHODS A systematic review of PubMed/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Therefore, the plateletpheresis has become a routine procedure in most countries [11] , and more and more widely used in patient [12][13][14] . Because the instruments need to be imported at present, the parameters suitable for Chinese population are still improving and developing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the plateletpheresis has become a routine procedure in most countries [11] , and more and more widely used in patient [12][13][14] . Because the instruments need to be imported at present, the parameters suitable for Chinese population are still improving and developing.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were underlined by Tsai et al proving increased skeletal muscle cell viability and cell proliferation by shifting cells from the G1 phase to S1 phase and G2&M phases after PRP application, besides demonstrating increased protein expressions of cyclin A2, cyclin B1, cdk2 and PCNA [ 60 ]. A recent systematic review summed up the current scientific background as follows: (1) in the majority of studies, PRP treatment increased myocyte proliferation, growth factor expression (e.g., PDGF-A/B and VEGF), leukocyte recruitment, and angiogenesis in muscle models when compared to control groups; (2) PRP preparation techniques remain inconsistent across studies in the basic science literature; and (3) evidence from in vitro and in vivo basic science studies suggest that PRP has the potential to serve as an efficacious treatment modality that may expedite the healing process for muscular pathologies, based on observed effects at the cellular and tissue levels in treatment groups relative to control groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are differences in the effectiveness of PRP products depending on the manufacturing process 70,0 0,0 review summed up the current scientific background as follows: (1) in the majority of studies, PRP treatment increased myocyte proliferation, growth factor expression (e.g., PDGF-A/B and VEGF), leukocyte recruitment, and angiogenesis in muscle models when compared to control groups; (2) PRP preparation techniques remain inconsistent across studies in the basic science literature; and (3) evidence from in vitro and in vivo basic science studies suggest that PRP has the potential to serve as an efficacious treatment modality that may expedite the healing process for muscular pathologies, based on observed effects at the cellular and tissue levels in treatment groups relative to control groups [41]. While retrospective studies described complete healing and no significant advantage considering time off the pitch [57], Bubnov et al observed less pain and significantly faster return to play in a cohort study of 30 athletes [10].…”
Section: Prp Applicationmentioning
confidence: 99%
“…Given all these key aspects, over the past years a growing interest has been focused on biologic agents such as platelet-rich plasma (PrP) to complement the cell culture medium and/or significantly ameliorate musculoskeletal tissue healing (Hamid et al, 2014;Kunze et al, 2019). However, their real beneficial effect is still questioned (Grassi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%